Studies on the collective and feminine in Indo-European from a diachronic and typological perspective - Neri, Sergio, 1970-; Schuhmann, Roland, 1972- (Brill's studies in Indo-European languages & linguistics ;, 2014)
This volume contains thirteen contributions on the origin of the feminine gender and its relation to the collective in the Indo-European parent language. The Indo-European daughter languages have got mostly a three-gender system, however the early attested Anatolian languages owned only two genders. In this respect, it is debatable whether the feminine gender is primary or arose secondarily from another morphological category. Due to special morphological and morphosyntactic phenomena it is also questionable whether the neuter plural of the individual languages continues an inflectional category or it was rather grammaticalized from an original word formation category collective. The authors suggest different approaches on the question of the relationship between feminine and collective.